1983
DOI: 10.1121/1.390154
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the acoustic nonlinearity parameter B/A from phase measurements

Abstract: A technique for measurement of the acoustic nonlinearity parameter B/A in liquids is presented, along with results for several liquids. The nonlinearity parameter is determined by measuring changes in the travel time of ultrasonic tone bursts which are caused by prescribed changes in the ambient pressure. The travel time differences are measured by comparing the phase of the tone burst with that of a reference signal. The measurement is simpler to perform than those previously reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…This parameter is important for two reasons: it is a basic parameter of a fluid, which can be related to the molecular dynamics of the medium, and it determines the distortion of a finite amplitude wave traveling through the fluid [47]. Indeed, it is a measure of the variation of the medium caused by the sound field [48], and can be used as a complementary parameter in the characterization of liquids [49].…”
Section: Resultsmentioning
confidence: 99%
“…This parameter is important for two reasons: it is a basic parameter of a fluid, which can be related to the molecular dynamics of the medium, and it determines the distortion of a finite amplitude wave traveling through the fluid [47]. Indeed, it is a measure of the variation of the medium caused by the sound field [48], and can be used as a complementary parameter in the characterization of liquids [49].…”
Section: Resultsmentioning
confidence: 99%
“…A thermodynamic method (Coppens et al 1965;Zhu et al 1983) and a finite-amplitude method (Gong et al 1989;Law et al 1985) are most commonly used to measure this parameter for liquid and liquid-like media. It has been reported that, compared with the linear ultrasonic parameters, the acoustic nonlinearity parameter B/A can provide more information on the state of the tissues and may become a novel parameter for biological tissue characterization (Bjørnø 1986;Gong et al 1993;Law et al 1985;Muir and Carstensen 1980;Sehgal et al 1986;Yoshizumi et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The B/A of water has previously been characterized up to 100°C [6][7][8][9][10]. However, emerging applications such as geothermal and petroleum industry downhole acoustic nonlinear imaging require knowledge of B/A of fluids at higher temperatures and pressures.…”
Section: Introductionmentioning
confidence: 99%